Commercialisation strategy in biotechnology start-ups : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Business and Administration at Massey University, Palmerston North, New Zealand - Dixon, Margaret Janette (Massey University, 2009)
The biotech sector has accumulated losses of around US$40 billion since its inception in the mid-1970s. The reasons for this may lie with the science itself, with organization and strategy, with the underlying costs of developing biotechnologies and/or with the institutional environment that biotech firms operate within. This thesis assumes that better organization and commercialisation strategy will improve overall returns in the biotech sector and asks the fundamental questions ‘how do biotech firms do strategy?’ and ‘how can biotech firms do strategy better?’ Strategy is the domain of the strategic management literature. Contributions to the literature that bear directly on commercialisation strategy in the biotech sector are examined. The sector’s unique institutional context is found to create an environment of high-risk and high-uncertainty. The real options reasoning and dynamic capabilities literatures provided some useful ideas for strategy in this context. Overall, the literature identifies a shortfall in directly actionable advice for biotech practitioners. Thus, the ‘great divide’ between academic research and practice is discussed. This thesis seeks to narrow the gap by synthesizing academic theory and practitioner knowledge on commercialisation strategy in the biotech sector in the way that will extend the strategic management literature and provide a process to aid practitioners in strategic decision making. A two phase methodological approach is employed that begins with a historical review of the development of the biotech sector and three in-depth case studies. Strategic issues facing biotech start-ups at the industry-level and firm-level are examined and related to the business models that firms adopt as an embodiment of their commercialisation strategies. A solid understanding of this relationship is then combined with real options reasoning and theory on dynamic capabilities to propose a model that may help biotech practitioners improve their approach to commercialization strategy. The model is refined and validated in a second phase of research involving interviews with seasoned veterans of the biotech sector. The Commercialisation Options Model is the final output of this research.
Keywords: Biotechnology industry; Strategic management; Biotechnology start-ups; Commercialisation options model; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290101 Fermentation, biotechnology and industrial microbiology